Family-Centered Care as A Cadre Empowerment Strategy For Early Detection Of High-Risk Pregnancies in The Community - Fitriana Kurniasari Solikhah; Taufan Arif; Maria Diah Ciptaning Tyas (Inovasi Lokal, 2026)
High-risk pregnancies remain a significant contributor to maternal complications and elevated maternal mortality rates, necessitating early detection efforts that involve communities and families. This community service program aimed to enhance the knowledge and skills of community health cadres in early detection of high-risk pregnancies using a Family-Centered Care (FCC) approach in the working area of Wagir Primary Health Center, Malang Regency. Methods used included health education, training on the use of screening forms, simulation exercises, family education sessions, and on-site mentoring of cadres at integrated health posts (posyandu). Evaluation was conducted using a pretest-posttest design among 64 health cadres. Results showed an increase in the average knowledge score from 54.90 at pretest to 88.75 at posttest. In addition, cadres demonstrated the ability to identify pregnancy risk factors, detect pregnant women in the high-risk category, and coordinate with village midwives for case follow-up. Family involvement in pregnancy monitoring also increased through improved awareness of danger signs and greater support for antenatal care visits. Statistical analysis showed that Family-Centered Care-based training and mentoring are effective in enhancing cadre capacity and family participation in the early detection of high-risk pregnancies. This program can serve as a community empowerment strategy that supports the prevention of pregnancy complications and the sustainable improvement of maternal health.